2019
DOI: 10.1039/c9cc06615b
|View full text |Cite
|
Sign up to set email alerts
|

A pyrophosphate-activated nanochannel inspired by a TRP ion channel

Abstract: An artificial pyrophosphate (PPi) selectively activated nanochannel has been successfully constructed via introducing calix[4]arene receptors into a biomimetic nanochannel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Figure S1 shows that scanning electron microscopy (SEM) indicated that the large opening of the nanochannel was about 480 nm with a so-called base ( D base ), while the electrochemical method measured that the small opening called tip ( d tip ) was about 18 nm. , The nanochannel interior surface was then functionalized. First, EDA was immobilized to the nanochannel inner surface through a coupling reaction (Figure a).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Figure S1 shows that scanning electron microscopy (SEM) indicated that the large opening of the nanochannel was about 480 nm with a so-called base ( D base ), while the electrochemical method measured that the small opening called tip ( d tip ) was about 18 nm. , The nanochannel interior surface was then functionalized. First, EDA was immobilized to the nanochannel inner surface through a coupling reaction (Figure a).…”
Section: Results and Discussionmentioning
confidence: 99%
“…It is well known that the ion transport behavior can be regulated by the surface charge of the nanochannels. 53,54 To S2 †) based on finite element method (FEM) combining with Poisson and Nernst-Planck (PNP) equations 55,56 (please see the Experimental section in supplementary information) were employed to simulate the Arg sensing process in β-CD-CuTCA/TiO 2 M. To calculate the ion distribution, the Comsol Multiphysics 5.5 was used with the "electrostatics (Poisson equation)" and "Nernst-Planck without Electroneutrality" modules. As schematically presented in Fig.…”
Section: Nanofluidic Simulations To Insight the Mechanism Of Signal M...mentioning
confidence: 99%
“…Although PI films [97,[112][113][114] were not applied as frequently as PET films, PI nanochannels can provide a highly stable ion current signal [115,116] and high surface charge density [54] comparable to PET. For example, Guo et al [117] demonstrated the salinity gradient energy harvesting on a non-biological single channel nanofluidic with PI membrane, and achieved ultrahigh power density.…”
Section: Homopolymer Nanochannelsmentioning
confidence: 99%
“…Diverse ion-responsive nanochannels such as K + [112,167] [81], and Cl − [171] have been investigated in the recent years. Yang et al [104] prepared a single conical nanochannel from 4-amino benzamidoxime (ABX) and PI membrane.…”
Section: Ion-responsive Nanochannelsmentioning
confidence: 99%